Pengaruh Media Sosial, Literasi Keuangan, dan Tren E-Commerce Selama Pandemi Covid 19 Terhadap Perilaku Konsumtif Mahasiswa (Studi Pada Mahasiswa Universitas Pembangunan Nasional “Veteran” Jawa Timur) - Nio Indra Satata; Muhadjir Anwar (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study aims to determine the effect of social media, financial literacy, and e-commerce models on consumptive behavior. During this pandemic period, students with high needs are also faced with conditions where lectures must be online and also online communication that makes high consumptive behavior. The method in this research uses stratification random sampling. Population in this study were all active undergraduate students at the National Development University "Veteran" East Java which were divided into several strata based on faculties with a total sample of 100 respondents. This research uses data collection method by spreading and using Smart PLS as a data analysis tool. The results of this study show that (1) social media contributes to the consumptive behavior of students and this contribution has a significant impact, (2) financial literacy not contributes to consumptive behavior, (3) e-commerce commerce has contributed to the consumptive behavior of students and the contribution made has a large and meaningful impact.